Employee Performance: QWL, Communication, and Work Discipline at Detention Center: Kinerja Karyawan: QWL, Komunikasi, dan Disiplin Kerja di Pusat Penahanan Imigrasi - Dina Maria Sofa; Mudji Astuti (Academia Open, 2023)
This research aimed to determine the influence of quality of work life (QWL), communication, and work discipline on performance at the Surabaya immigration detention center, Ministry of Law and Human Rights, East Java Regional Office. This was a quantitative research with hypothesis testing, using multiple linear regression analysis with SPSS version 18 for Windows. The sample consisted of 52 staff members at the immigration detention center in Surabaya. Primary data was collected through a questionnaire using a Likert scale that was tested for validity and reliability. The results of this research showed that QWL, communication, and work discipline have a significant influence on employee performance. Additionally, QWL, communication, and work discipline have a simultaneous effect on employee performance. Highlights : QWL, communication, and work discipline have a significant influence on employee performance at the Surabaya immigration detention center. The study used a quantitative research design with hypothesis testing and multiple linear regression analysis to examine the relationship between QWL, communication, work discipline, and employee performance. The results highlight the importance of addressing QWL, communication, and work discipline in promoting employee performance in detention center settings. Keywords: Quality of Work Life (QWL), Communication, Work Discipline, Employee Performance, Immigration Detention Center.